An Investigation on Consumer Perceptions of Email and Social Media Marketing: An Advertising Case in South Africa - de la Roche , Caitlin; de Barros , Tiago; Chuchu, Tinashe; Nyagadza, Brighton; Venter de Villiers, Marike (International Review of Management and Marketing, 2022)
Due to the increasing usage of digital marketing to advertise to consumers in recent years, there has been a growing interest in determining which digital marketing channels are the most effective in not only successfully getting the brand message across to the consumer, but also generating the most return on investment in the form of greater consumer purchase intention. As such, the objective of this research was to determine how the antecedents, perceived benefit, perceived risk, and organisational trust influenced consumer attitudes towards these two digital marketing channels. Furthermore, the effect of consumer attitudes on consumer purchase intention and hence post-purchase behaviour were also examined. The research was conducted using a quantitative approach by means of a survey in the forms of a questionnaire that was distributed to participants using a combination of the convenience and snowball sampling methods. A sample size of 262 respondents was used, and the requirements to participate in the study were for the individual to be over the age of 18 and be a consumer based in South Africa. The data was subsequently analysed using SPSS 27 for descriptive analysis and hypothesis testing respectively. The proposed hypotheses were tested to understand the relationships between the study’s constructs. Ultimately, the study found that consumers who form a positive attitude towards a brand advertising via email or social media will have a higher intention to purchase the brand, and will more likely make repeat purchases of that brand. The limitations of the study are discussed and future research direction is proposed.